2018
DOI: 10.1073/pnas.1810582115
|View full text |Cite
|
Sign up to set email alerts
|

SOG1 activator and MYB3R repressors regulate a complex DNA damage network in Arabidopsis

Abstract: SignificanceDNA damage triggers a highly conserved response that coordinates processes necessary to maintain genome integrity, including cell cycle arrest, DNA repair, and cell death. Despite the identification of primary transcription factors (TFs) that control these processes, knowledge regarding the downstream genes and regulatory networks controlled by these TFs remains poorly understood. Using Arabidopsis, we generated the first model of the DNA damage response transcriptional network, revealing 11 coexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
186
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(213 citation statements)
references
References 106 publications
(208 reference statements)
5
186
1
Order By: Relevance
“…Briefly, 6-d-old PIF7-HA (Galvao et al, 2019) seedlings grown in LD at 21°C were either kept at 21°C or shifted at ZT2 to 28°C for 2 h before harvesting in liquid nitrogen. Chromatin extraction was performed as described previously (Bourbousse et al, 2018) except that samples were crosslinked only with formaldehyde. Immunoprecipitation was performed as described previously (Gendrel et al, 2005) using an anti-HA antibody (Santa Cruz Biotechnology, Inc., Dallas, TX, USA; sc-7392 X).…”
Section: Chip-qpcrmentioning
confidence: 99%
“…Briefly, 6-d-old PIF7-HA (Galvao et al, 2019) seedlings grown in LD at 21°C were either kept at 21°C or shifted at ZT2 to 28°C for 2 h before harvesting in liquid nitrogen. Chromatin extraction was performed as described previously (Bourbousse et al, 2018) except that samples were crosslinked only with formaldehyde. Immunoprecipitation was performed as described previously (Gendrel et al, 2005) using an anti-HA antibody (Santa Cruz Biotechnology, Inc., Dallas, TX, USA; sc-7392 X).…”
Section: Chip-qpcrmentioning
confidence: 99%
“…One of the key findings in this study is that DNA damage induces the cytokinin biosynthesis genes IPT1, IPT3, IPT5, IPT7, LOG7 and CYP735A2. Since these genes are not among the SOG1 target genes previously identified by ChIP-seq analyses 11,12 , downstream transcription factor(s) are likely involved in their induction. The promoter:GUS lines showed that IPT1 expression increased in zeocin-treated roots, while IPT3 and IPT5 were induced in cotyledons and shoot apices, respectively ( Fig.…”
Section: Discussionmentioning
confidence: 97%
“…ChIP-qPCR analyses were performed with an anti-H3K4me3 antibody and with antihistone H3 to normalize levels to nucleosome occupancy. H3K4me3/H3 levels are given as percentages of IP/input input relative to the mean signals over two housekeeping genes (At4g23100 and At4g22330) with no change in expression and in H3K4me3 level during the transition [96]. Error bars correspond to standard deviations from two replicates.…”
Section: S2lb Associates With Highly Transcribed Genes and Is Requirementioning
confidence: 99%
“…Profiling of S2Lb-GFP and MYC-SDG2 was performed using anti-GFP (Life Technologies #11122) and anti-MYC (Ozyme #71D10) antibodies, respectively, and two crosslink steps. As recently described [96], samples were cross-linked first with 1.5 mM ethylene glycol bis(succinimidyl succinate) for 20 min and then with 1% formaldehyde for 10 min at room temperature. Cross-linking was stopped by adding 1.7 mL of 2 M glycine and incubating for 10 min.…”
Section: Chip-qpcr Chip-sequencing and Chip Bioinformaticsmentioning
confidence: 99%